Territórios marginais dos desejos: dissidências, resistências e prostituição feminina - Silva, Luciana Codognoto da [UNESP]; Justo, José Sterza [UNESP]; Peres, Wiliam Siqueira [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2015)
In this research, we discuss important aspects related to the scope of the adult female prostitution in a municipality located in the State of São Paulo, Brazil. We rely on the theoretical contributions provided by the Cultural Studies, the Queer Theory and other aspects referenced by gender studies, by sexualities and other subjective processes, in parallel with the analysis of the reported life stories of two women linked to the context of commercial sexual practice in the studied city. From the presented informations, we observed multiple stories of women in the process of resistance to some standards of femininity, and come to the conclusion that the economic factor is not always preponderant for the entry/residence in female commercial sex practice, especially today, when relationships tend be established by the confluence of multiple interests.

Nesta pesquisa, buscamos problematizar importantes aspectos ligados ao âmbito da prostituição feminina adulta em um município localizado no interior do Estado de São Paulo. Utilizamo-nos das contribuições teóricas elencadas pelos Estudos Culturais, pela Teoria Quer e demais vertentes referenciadas pelos estudos de gêneros, pelas sexualidades e processos de subjetivação em paralelo à análise de relatos de histórias de vida de duas mulheres vinculadas ao contexto da prática sexual comercial no município pesquisado. A partir das informações apresentadas, observamos as múltiplas histórias de mulheres em vias de resistências a dados padrões de feminilidade, onde o fator econômico nem sempre atuará com preponderância para a entrada/permanência feminina na prática sexual comercial, especialmente, hoje, quando os relacionamentos tendem a ser estabelecidos pela confluência de interesses múltiplos.
Marginal wishes territories: dissent, resistance and female prostitution
Keywords: Corporeality; Processes subjectivity; Prostitution women; Corporalidades; Processos de subjetivação; Prostituição feminina